BATCH SETTLING IN VERTICAL SETTLERS - Lama Ramirez, R. (1998)
lt has been studied the batch sedimentation of aqueous suspensions of precipitated calcium carbonate, barium sulphate and lead oxide , in vertical thickeners of rectangular and circular cross sectional area. Suspensions vary in concentration between 19.4 and 617.9 g/I and the rate of sedimentation obtained between 0.008 and 7.70 cm/min. The effect of the specific gravity of the solid on the rate of sedimentation is the same for all the suspensions, that is, the greater the value of the specific gravity the greater the value of rate of sedimentation.